2021
DOI: 10.3390/pathogens10091134
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis and Immune Evasion of Vesicular Stomatitis New Jersey Virus Inferred from Genes Expression Changes in Infected Porcine Macrophages

Abstract: The molecular mechanisms associated with the pathogenesis of vesicular stomatitis virus (VSV) in livestock remain poorly understood. Several studies have highlighted the relevant role of macrophages in controlling the systemic dissemination of VSV during infection in different animal models, including mice, cattle, and pigs. To gain more insight into the molecular mechanisms used by VSV to impair the immune response in macrophages, we used microarrays to determine the transcriptomic changes produced by VSV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 115 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…We recently reported on genes induced by primary swine macrophages infected with the field isolate to infer VSV molecular pathogenesis [ 27 ]. In this study, our biological pathway analyses of DEGs identified several pathways associated with the type I IFN response (including activation, signaling, induction, and antiviral mechanisms), which was consistent with previous in vitro and in vivo experiments that demonstrated the susceptibility of VSV to the action of type I IFN [ 22 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently reported on genes induced by primary swine macrophages infected with the field isolate to infer VSV molecular pathogenesis [ 27 ]. In this study, our biological pathway analyses of DEGs identified several pathways associated with the type I IFN response (including activation, signaling, induction, and antiviral mechanisms), which was consistent with previous in vitro and in vivo experiments that demonstrated the susceptibility of VSV to the action of type I IFN [ 22 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mock-infected samples were incubated in the same conditions with macrophage media in triplicate. The incubation time was determined based on previous studies performed on primary porcine macrophages [ 22 , 23 , 27 ]. It is supported by the ability of VSV to induce high levels of gene expression in primary porcine macrophages infected with a high MOI, avoiding the presence of the cytopathic effect, a condition that decreases the RNA yields.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations